2016
DOI: 10.1007/s10661-015-5047-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical parameter correlations with technical and technological characteristics of heating systems and the presence of Legionella spp. in the hot water supply

Abstract: The purpose of this study was to evaluate the prevalence of Legionella spp. and compare the quality of hot water between four facilities for accommodation located in Southern Croatia (the Split-Dalmatian County). The research included data collection on the technical and technological characteristics in the period from 2009 to 2012. The survey included a type of construction material for the distribution and internal networks, heating system water heater type, and water consumption. Changes in water quality we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
1
8
2
Order By: Relevance
“…There have been numerous studies which have linked potable water to outbreaks of Legionellosis [ 6 , 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, there have also been numerous studies which have detected the pathogen from potable water not associated with a specific outbreak; this includes studies from the U.S. [ 24 , 25 ], The Netherlands [ 26 , 27 , 28 ], Germany [ 29 , 30 ], Sweden [ 31 ], Israel [ 32 ], Australia [ 33 ], Latvia [ 34 ], Italy [ 35 ], Spain [ 36 ], UK [ 37 ], Croatia [ 38 ], France [ 39 ], Iran [ 40 ] and China [ 41 ]. A recent study by Donohue [ 42 ] collected 272 water samples from public and private cold water taps across the U.S. and found that 47% were positive for L. pneumophila Sg1 using qPCR.…”
Section: The Presence Of Legionella In Potable mentioning
confidence: 99%
“…There have been numerous studies which have linked potable water to outbreaks of Legionellosis [ 6 , 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, there have also been numerous studies which have detected the pathogen from potable water not associated with a specific outbreak; this includes studies from the U.S. [ 24 , 25 ], The Netherlands [ 26 , 27 , 28 ], Germany [ 29 , 30 ], Sweden [ 31 ], Israel [ 32 ], Australia [ 33 ], Latvia [ 34 ], Italy [ 35 ], Spain [ 36 ], UK [ 37 ], Croatia [ 38 ], France [ 39 ], Iran [ 40 ] and China [ 41 ]. A recent study by Donohue [ 42 ] collected 272 water samples from public and private cold water taps across the U.S. and found that 47% were positive for L. pneumophila Sg1 using qPCR.…”
Section: The Presence Of Legionella In Potable mentioning
confidence: 99%
“…As a result, factors affecting the prey community will have consequences on the Legionella host community, and therefore, indirectly on the Legionella community. Accordingly, competition between prey species and non-prey species, competition by predation for the same prey by the non-Legionella host community and chemical and physical parameters of the environments are all elements that can have negative effects on the prey community [37][38][39]. For instance, Bdellovibrio spp.…”
Section: Introductionmentioning
confidence: 99%
“…36 With an ideal growth range between 28 and 40 °C, 37 heated water systems are thought to serve as the primary source for Legionella occurrence and transmission, although a wide variety of sources have been linked to legionellosis. 38 Many engineered water systems tend to have physical conditions conducive to Legionella , 39 biofilms they associate with, 40 and eukaryotic hosts they replicate within, 41 all factors commonly found and amplified in premise plumbing (i.e., that found in buildings such as homes, schools, and hospitals). 42 …”
Section: Introductionmentioning
confidence: 99%